2023
DOI: 10.3390/toxics11020139
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, Sources and Risk Assessment of Polychlorinated Biphenyls in Sediments from Beiluo River

Abstract: The distribution and source of polychlorinated biphenyls (PCBs) pollution in the Beiluo River, the secondary tributary of the Yellow River, still remain unclear. With the purpose of determining the distribution, origins, and pollution levels of PCBs and their consequences on ecological risks, the concentrations of 27 PCBs at 17 locations in the sediments of the Beiluo River were examined in this study. The results showed that the mass concentrations of ∑PCBs in the sediment ranged from 0.12 to 1.25 ng∙g−1 (DW)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 59 publications
1
10
1
Order By: Relevance
“…To compare the evaluated PCBs concentrations with reports from other studies is complex due to differences in PCBs congeners selected and the statistical methods used. However, comparing the total PCBs concentrations observed in this study (252 -3,977 µg/kg) with other related studies showed that the result obtained in this study was relatively higher for sediments in Nigeria 0.026 -0.198 µg/kg [28], China 1.75 -92.27 µg/kg [29], China 16.15 -477.85 µg/kg [30], and China 0.12 -1.25 µg/kg [26]. There is a significant statistical difference of p < 0.01 and p > 0.05 between Sites across seasons.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…To compare the evaluated PCBs concentrations with reports from other studies is complex due to differences in PCBs congeners selected and the statistical methods used. However, comparing the total PCBs concentrations observed in this study (252 -3,977 µg/kg) with other related studies showed that the result obtained in this study was relatively higher for sediments in Nigeria 0.026 -0.198 µg/kg [28], China 1.75 -92.27 µg/kg [29], China 16.15 -477.85 µg/kg [30], and China 0.12 -1.25 µg/kg [26]. There is a significant statistical difference of p < 0.01 and p > 0.05 between Sites across seasons.…”
Section: Resultssupporting
confidence: 71%
“…Where C i f = the pollution index of a pollutant, C i = the determined concentration of contaminants in sediments, ni = the global contaminant level in the pre-industrial sediments for each pollutant (10 µg/kg) and Ti = toxic response parameters for each pollutant in the study according to the standardization developed by Montuori et al [16] and Han et al [26]. The classification of the risk levels follows Eri < 40 is a minor ecological hazard, 40 < Eri is a medium ecological hazard, 80 ≤ Eri ≤ 40 is a strong ecological hazard, 160 ≤ Eri ≤ 320 is a very strong ecological hazard, Eri > 320 is pole strength ecological hazard [26].…”
Section: Potential Ecological Risk Evaluationmentioning
confidence: 99%
“…The surrogate recoveries were 69.46% ± 32.81%, 82.14% ± 6.46%, and 79.00% ± 12.71% for TCMX, PCB65, and PCB155, respectively. The results showed that this experiment was feasible for the treatment of samples [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…As a result, agricultural products such as pesticides and fertilizers are used in large quantities, leading to serious organic pollution in the Beiluo River Basin, threatening the environment and human health in the basin [16]. Currently, studies of this basin mainly focus on monitoring indicator organisms (such as zooplankton) and water quality evaluation [16,17], while there are few studies on organic pollution [18]. Magulova et al proposed that POP monitoring data are essential to establish a global baseline of POP levels and predict changes in POP concentrations [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation